Postmortem concentrations of gamma-hydroxybutyrate (GHB) in peripheral blood and brain tissue — Differentiating between postmortem formation and antemortem intake. (March 2017) - Thomsen, Ragnar; Rasmussen, Brian Schou; Johansen, Sys Stybe; Linnet, Kristian
Highlights: Postmortem blood and brain GHB concentrations in 221 autopsy cases are presented. Brain samples were extracted from gray matter in the cerebral cortex of the frontal lobe. Consideration of decomposition level is important in the interpretation of GHB intoxications. Brain is proposed as a useful matrix for identification of GHB intake. A cut-off of 10 mg/kg for brain tissue may be appropriate in cases with limited decomposition. Abstract: Gamma -hydroxybutyrate (GHB) is a recreational drug, a drug of abuse, as well as an endogenous molecule in mammals. The drug has become infamous as a tool for drug-facilitated sexual assault. GHB is found in low concentrations in living humans, while at postmortem the concentration of GHB rises due to fermentation processes. The endogenous nature of GHB leads to difficulty in interpretation of concentrations, as the source of GHB is not obvious. Postmortem brain and blood samples were collected from 221 individuals at autopsy. Of these, 218 were not suspected of having ingested GHB, while GHB intake was reported for the last three (cases A–C). Decomposition level was estimated and cases classified into no/minor and advanced decomposition. Brain samples were extracted from the frontal lobe; only gray matter from the cerebral cortex was used. Blood was drawn from the femoral vein. Brain samples were homogenized and diluted with water. Brain homogenates or femoral blood were then prepared using protein precipitation and GHB was quantified with UHPLC–MS/MS. For 189 cases where ingestion of GHB was not suspected and where no/minor decomposition had occurred the concentrations were in the range 4.8–45.4 mg/kg (median 15.3 mg/kg) in blood and not-detected to 9.8 mg/kg (median 4.8 mg/kg) in brain tissue. For case A, where intoxication with GHB was deemed to be the sole cause of death, the concentrations were 199 and 166 mg/kg in blood and brain, respectively. For case B, where intoxication with GHB was a contributing factor of death, the respective concentrations were 142 and 78.4 mg/kg. For case C, where GHB was ingested but the cause of death was opioid poisoning, the concentrations were 40.3 and 12.7 mg/kg. The results demonstrate that postmortem-formed levels of GHB are much lower in brain than peripheral blood. Analysis of GHB in brain tissue thus provides for an improved capability to identify an exogenous source of GHB. By measuring GHB in brain tissue and employing a cut-off concentration of 10 mg/kg, a tentative distinction can be made between an endo- and exogenous source of GHB. An exception to this strategy is for extensively decomposed corpses, where endogenous GHB concentrations can be high even in brain.